Aplikasi Pemesanan Air Galon Online Dengan Fitur Tracking Posisi Pengantar Galon Berbasis Android - Syukria Fiki; Indri Rahmayuni; Deddy Prayama (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2021)
Water is a basic human need that plays the most important role in human life in order to sustain human life. As time goes by, the need for clean water is very much needed by the community. The high need for water is the driving force for practical drinking water. In this final project, the application is made using Android Studio as a text editor, Sublime as a text editor to create an API, and MySQL which is useful as a system manager on the database on the server. In the application there is access as a customer, depot owner and as an introduction to gallons. The customer will then process the gallon water order and the depot owner will process the order that has been placed by the customer and send the order data to the gallon controller. When the gallon delivery person delivers the order, the customer can access the gallon delivery tracking process. Keywords: Android java, API, Tracking